Reducing foreclosures: No easy answers - Christopher L. Foote; Kristopher Gerardi; Lorenz Goette; Paul Willen (Federal Reserve Bank of Atlanta, 2009)
This paper takes a skeptical look at a leading argument about what is causing the foreclosure crisis and what should be done to stop it. We use an economic model to focus on two key decisions: the borrower's choice to default on a mortgage and the lender's subsequent choice whether to renegotiate or modify the loan. The theoretical model and econometric analysis illustrate that unaffordable loans, defined as those with high mortgage payments relative to income at origination, are unlikely to be the main reason that borrowers decide to default. In addition, this paper provides theoretical results and empirical evidence supporting the hypothesis that the efficiency of foreclosure for investors is a more plausible explanation for the low number of modifications to date than contract frictions related to securitization agreements between servicers and investors. While investors might be foreclosing when it would be socially efficient to modify, there is little evidence to suggest they are acting against their own interests when they do so. An important implication of our analysis is that policies designed to reduce foreclosures should focus on ameliorating the immediate effects of job loss and other adverse life events rather than modifying loans to make them more affordable on a long-term basis.
Keywords: D11; D12; G21; 330; mortgage; foreclosure; modification; securitization; Hypothek; Subprime-Hypothek; Finanzmarktkrise; Securitization; Zwangsvollstreckung; USA